A three-dimensional metal grid mesh as a practical alternative to ITO. Issue 29 (12th July 2016) - Jang, Sungwoo; Jung, Woo-Bin; Kim, Choelgyu; Won, Phillip; Lee, Sang-Gil; Cho, Kyeong Min; Jin, Ming Liang; An, Cheng Jin; Jeon, Hwan-Jin; Ko, Seung Hwan; Kim, Taek-Soo; Jung, Hee-Tae
Abstract : The development of a practical alternative to indium tin oxide (ITO) is one of the most important issues in flexible optoelectronics. Abstract : The development of a practical alternative to indium tin oxide (ITO) is one of the most important issues in flexible optoelectronics. In spite of recent progress in this field, existing approaches to prepare transparent electrodes do not satisfy all of their essential requirements. Here, we present a new substrate-embedded tall (∼350 nm) and thin (∼30 nm) three-dimensional (3D) metal grid mesh structure with a large area, which is prepared via secondary sputtering. This structure satisfies most of the essential requirements of transparent electrodes for practical applications in future opto-electronics: excellent optoelectronic performance (a sheet resistance of 9.8 Ω □ −1 with a transmittance of 85.2%), high stretchability (no significant change in resistance for applied strains <15%), a sub-micrometer mesh period, a flat surface (a root mean square roughness of approximately 5 nm), no haze (approximately 0.5%), and strong adhesion to polymer substrates (it survives attempted detachment with 3M Scotch tape). Such outstanding properties are attributed to the unique substrate-embedded 3D structure of the electrode, which can be obtained with a high aspect ratio and in high resolution over large areas with a simple process. As a demonstration of its suitability for practical applications, our transparent electrode was successfully tested in a flexible touch screen panel. We believe that our approach opens up new practical applications in wearable electronics.